Digital Humanities and Multisentric Law: an Interdisciplinary Approach to Resolving Land Disputes Between PT Rapp and The Dayun Community - Rahmiati Rahmiati; Ghazza Jaudat Fastmadhi; Nazwa Svenska Aulia Fastmadhi; Deddi Fasmadhy Satiadharmanto (Green Publisher, 2025)
The research demonstrates that mediation respecting customary traditions is more effective than formal legal approaches that disregard the socio-cultural context.( Miller et al.” Supervising Minorities—Respecting Individual and Cultural Differences”, Effective Police Supervision – 2020). This highlights the significance of the multisentric law approach, where legal processes must be open to social and cultural norms to achieve more satisfactory outcomes for the community. In the context of digital humanities, technology can be leveraged to support dispute resolution through digital mapping and more detailed analysis of cultural data. The use of digital mapping to visually document customary land claims can help clarify conflicts and improve accuracy in the mediation process.( Pratiwi & Juerges, “Digital advocacy at the science-policy interface: Resolving land-use conflicts in conservation forests”, Land Use Policy – 2022). Integrating digital technology with legal and cultural approaches would result in a more comprehensive and inclusive resolution, as shown by the study's findings (with over 70% of respondents satisfied with mediation based on customary practices). The interdisciplinary approach combining digital humanities and multisentric law creates a land dispute resolution process that is more relevant to the socio-cultural context of the local community. (Wang & Chen ,” From alternative dispute resolution to pluralist dispute resolution: towards an integrated dispute-resolution mechanism in China”, International Journal of Law in Context – 2020).This ensures that the solutions are not only legally valid but also accepted by the community, thereby enhancing the legitimacy and effectiveness of the mediation process.